PERBANDINGAN EFEKTIVITAS TRAMADOL DENGAN KOMBINASI TRAMADOL + KETOLORAC PADA PENANGANAN NYERI PASCA SEKSIO SESAREA - Fajarini, Ayu Y. S.; Kumaat, Lucky; Laihad, Mordekhai (e-CliniC, 2014)
Abstract: Cesarean delivery is often associated with post-operative pain; therefore pain control drugs are  commonly needed. Population of more than 30 cases of cesarean section has been selected according to inclusion and exclusion criteria. The population was divided into 2 groups: group I for the administration of tramadol 2 mg/g IV and group 2 for the administration of tramadol 1 mg/kg IV combined with ketorolac 30 mg/kg IV. After the cesarean delivery, pain levels were measured by using the Bourbonais scale at 1 hour and 3 hours after the first administration, and then one hour after the second administration for both groups.  Data were analyzed by using the Statistical Product and Service Solution Program (SPSS) and the paired-t-test. The results showed that between the two groups there was no difference in pain case numbers after one hour of the first administration. After 3 hours of the first administration, there was 1 case (6.67%) of mild pain in group I compared with 9 cases (60%) in the group II. Moreover, there were 5 cases of severe controlled pain in group I compared with 0 case in group II. A statistical analysis using the paired t-test showed a P of 0.00.  Conclusion: As a pain killer drug,tramadol was more effective in severe controlled pain cases, but less efffective in mild pain cases than the combination of tramadol and ketolorac. Keywords: general anesthesia, Cesarean section, pain level, tramadol, ketorolac   Abstrak: Persalinan secara bedah sesar sering kali dihubungkan dengan nyeri pasca operasi yang membutuhkan obat-obat penghilang nyeri. Populasi sebanyak 30 kasus bedah sesar yang dipilih sesuai kriteria inklusi dan eksklusi. Populasi dibagi menjadi 2 kelompok, yakni kelompok I untuk pemberian tramadol 2 mg/kgBB IV dan kelompok 2 untuk kombinasi tramadol 1 mg/kgBB IV dan ketorolac 30 mg/kgBB IV. Setelah menjalani bedah sesar, tingkat nyeri diukur dengan menggunakan skala Bourbonais 1 jam dan 3 jam setelah pemberian dosis 1, dan 1 jam setelah pemberian dosis ke-2 untuk kedua kelompok. Data dianalisis dengan menggunakan SPSS dan uji paired-t-test. Hasil penelitian memperlihatkan tidak terdapat perbedaan jumlah kasus nyeri pada 1 jam setelah pemberian obat dosis 1 antara kedua kelompok. Terdapat perbedaan jumlah kasus nyeri ringan pada 3 jam setelah pemberian obat dosis 1, yaitu 1 kasus (6,67%) pada kelompok I dibandingkan 9 kasus (60%) pada kelompok II. Untuk kasus nyeri berat terkontrol, terdapat 5 kasus (33,3%) pada kelompok I dibandingkan 0 kasus (0%) pada kelompok II. Analisis statistik menggunakan paired-t test memperlihatkan P = 0,00. Simpulan: Sebagai obat penghilang nyeri, tramadol lebih efektif  pada kasus nyeri berat terkontrol, tetapi lebih kurang efektif pada nyeri ringan dibandingkan kombinasi tramadol dan ketorolac. Kata kunci: anestesi umum, seksio sesarea, tingkat nyeri, tramadol, ketorolac